Cognitive Functions in Middle-Aged Patients with Manifestations of Metabolic Syndrome - Khramtsov, D.; Chernyshov, O.; Nazarian, V.; Dobush, I. (Journal of Education, Health and Sport, 2025)
Background. Metabolic syndrome (MS) is a major contributor to cardiovascular and endocrine morbidity and has increasingly been implicated in neurodegenerative processes. However, early cognitive alterations in middle-aged individuals with MS often remain clinically overlooked. Objective. To assess cognitive functions and their associations with metabolic and vascular parameters in middle-aged patients with metabolic syndrome. Materials and Methods. A total of 86 middle-aged patients with MS diagnosed according to IDF (2005) criteria and 50 age- and sex-matched healthy controls were enrolled. All participants underwent comprehensive clinical and laboratory evaluation, including anthropometric measurements, blood pressure, lipid profile, fasting glucose and insulin levels, and calculation of HOMA-IR. Cognitive functioning was assessed using a standardized neuropsychological battery (MMSE, MoCA, Trail Making Test A/B, Digit Span). Cerebrovascular and endothelial status were evaluated by carotid intima–media thickness and endothelial function testing. Statistical analysis included parametric/nonparametric tests and correlation analysis. Results. Patients with MS demonstrated significantly lower cognitive performance compared with controls, with prominent deficits in executive functions, attention, working memory, and processing speed. The prevalence of mild cognitive impairment (MoCA < 26) was markedly higher in the MS group. Cognitive decline correlated strongly with insulin resistance, atherogenic dyslipidemia, arterial hypertension, endothelial dysfunction, and increased carotid intima–media thickness. A cumulative effect of MS components on cognitive outcomes was observed. Conclusions. Middle-aged patients with metabolic syndrome exhibit early, multidomain cognitive impairment closely associated with insulin resistance and cerebrovascular dysfunction. Routine cognitive screening in this population may facilitate early identification of individuals at elevated risk for cerebrovascular disease and cognitive decline and support timely preventive interventions.